Enhancing transformer windings monitoring: An approach using longitudinal branch‐circuit conductance analysis - Xiangping Kong; Zijun Bin; Jiansheng Li; Shiming Liu; Wenchen Zhao; Mengfei Wu (IET Generation, Transmission & Distribution, 2024)
Abstract The operating environment of transformers is getting more complex with the emergence of new energy sources and power electronic devices. This complexity can cause minor internal faults in transformer windings. Under the cumulative effect, minor faults gradually develop into serious faults, resulting in transformer damage. Conventional differential protection systems may have difficulty detecting these glitches and require avoiding the problem of protection false activation caused by inrush currents. This paper proposes a new online monitoring method for transformer windings based on longitudinal branch‐circuit conductance to address this issue. First, a unified transformer equivalent circuit is proposed to represent transformers under normal conditions, inrush currents, and internal faults. Then, an online transformer monitoring method based on branch conductance is proposed, which is immune to inrush currents. This method aims to prevent delayed detection of faults during inrush currents, improving sensitivity and response speed, especially for minor turn‐to‐turn faults hidden in inrush currents. The proposed method also provides higher sensitivity to minor turn‐to‐turn faults and larger protection margins. Simulation and experimental results validate the effectiveness of this method.